Historiography of Diplomacy and Foreign Policy: An Afrocentric Perspective - Nwala, Paul (Cascades, Journal of the Department of French & International Studies, 2024)
This paper explores the historiography of diplomacy and foreign policy through an Afrocentric lens, examining the complexities and nuances of diplomatic interactions involving African nations and their counterparts. Drawing on the rich tapestry of African history, culture, and intellectual traditions, the study offers a comprehensive analysis of how diplomatic relations and foreign policies have been interpreted, constructed, and understood from an Afrocentric perspective. The historiography of diplomacy and foreign policy from an Afrocentric viewpoint encompasses several key dimensions. It involves a critical examination of primary sources, including diplomatic archives, treaties, and correspondence, to uncover the agency and contributions of African actors in shaping global relations. This entails challenging Eurocentric narratives that often marginalize or overlook African perspectives and experiences in diplomatic history. The study examines the roles of African culture in shaping diplomatic interactions and foreign policies. It highlights the significance of cultural diplomacy and soft power in fostering crosscultural understanding and cooperation between African nations and the global community. The historiography of diplomacy and foreign policy from an Afrocentric perspective engages with the legacies of colonialism, imperialism, and neo-colonialism in shaping contemporary diplomatic dynamics in Africa. By centering African voices, experiences, and agency, it seeks to challenge dominant narratives and offer a more inclusive and holistic understanding of global diplomacy, illuminating the diverse ways in which African nations have shaped and been shaped by diplomatic interactions throughout history amongst others.